Intersections and Divergences Between Empathizing and Mentalizing: Development, Recent Advancements by Neuroimaging and the Future of Animal Modeling - Cerniglia, Luca; Bartolomeo, Letizia; Capobianco, Micaela; Lo Russo, Sara Lucia M.; Festucci, Fabiana; Tambelli, Renata; Adriani, Walter; Cimino, Silvia (Frontiers in Behavioral Neuroscience, 2019)
Both mentalization and empathy allow humans to understand others, through the representation of their mental states or their mood respectively. The present review aims to explain those characteristics which are shared between empathy and the Theory of Mind. Research in neuroscience, based on naturalistic paradigms, has shown that abilities to mentalize and to empathize are associated with the activation of different neuro-cognitive circuits. As far as mirror-neuron processes are concerned, some structures (like Anterior Insula, AI; Anterior Cingulate Cortex, ACC) play a role both in the representation of one’s own affective states and in the comprehension of the same affective state when experienced by others. As for mentalization, the temporal parietal junction (TPj) and temporal poles (TP), the upper posterior temporal sulcus (pSTS) and the medial prefrontal cortex (mPFC) are greatly involved: the latter appears involved in the attribution of one’s own and others’ temperaments. Interestingly, the ventral (orbital) prefrontal cortex (orbito-frontal cortex, OFC) is involved in subserving shared affective experience during cognitive mentalizing. This brain region represents a point of overlap, from a psycho-biological point of view, where emotional mirroring and affective cognition meet up. As for animal models, laboratory rodents can well be tested for prosocial behavior. Some examples include the deliberate action to let another conspecific have access to food: this willingness can vary across donors and depending on how the recipient is perceived. Other examples include the possibility to let a trapped conspecific come out (“giving help”). The state-of-the-art knowledge about this theme can inform the programming of specific clinical interventions, based on the reinforcement of empathic and/or mentalization abilities.